Intermittent Hypoxia-Induced Renal Antioxidants and Oxidative Damage in Male Mice: Hormetic dose Response. Issue 3 (1st July 2013) - Sun, Weixia; Yin, Xia; Wang, Yuehui; Tan, Yi; Cai, Lu; Wang, Bo; Cai, Jun; Fu, Yaowen
Obstructive sleep apnea causes cardiovascular disease via chronic intermittent hypoxia (IH), which may be related to oxidative stress. Nuclear factor-erythroid 2-related factor 2 (Nrf2) is an important cellular defense mechanism against oxidative stress by regulating its down-stream multiple antioxidants. The present study was to define whether IH can induce renal pathogenic damage and if so, whether Nrf2 and its down-stream antioxidants are involved in IH-induced pathogenic changes. Mice were culled for exposure to intermittent air as control or IH that consisted of 20.9% O2 /8% O2 FI O2 alternation cycles (30 episodes per h) with 20 seconds at the nadir FI O2 for 12 h a day during daylight. Short-term IH exposure (3 −7 days) induced significant increases in renal inflammatory response and antioxidant levels along with a reduction of the spontaneous content of malondialdehyde while long-term IH exposure (8 weeks) induced a significant decrease of antioxidant levels and significant increases of renal inflammation, oxidative damage, cell death, and fibrosis. This study suggests that IH induces a hormetic response, i.e.: short-term IH exposure is able to induce a protective response to protect the kidney from oxidative damage while long-term IH exposure is able to induce a damage effect on the kidney.